Knowledge, Attitude and Participation of People in Community Solid Waste Management, Khlongdan Subdistrict Municipality, Bang Bo District, Samut Prakan Province - Salapsri, Sureeporn; Bodeerat, Chot (Interdisciplinary Academic and Research Journal, 2023)
Solid waste is a global problem. This is caused by the country’s development, population, economic and social expansion, and the changing consumption behavior of the people, which has increased the amount of solid waste every year. Many areas are facing the problem of accumulated solid waste that is so large that it cannot be disposed of in time. It inevitably affects the environment and public health. The objectives of this research were 1) to study the level of knowledge, attitude, and people’s participation behavior in solid waste management, and 2) to compare their organizational commitment according to personal factors. This research applied Quantitative Research. The samples were 354 people from the calculation formula of Taro Yamane. The results were analyzed using descriptive statistics including frequency, percentage, mean and standard deviation. and inferential statistics, including t-test, F-test, and Pearson’s Correlation. The results of the research were as follows: (1) The level of knowledge of people in solid waste management in Khlong Dan Subdistrict Municipality was at a high level. People’s Attitude toward Solid Waste Management in Khlong Dan Sub-district Municipality was at a good level. And the level of people’s participation behavior in community solid waste management in Klong Dan Subdistrict municipality as a whole was at a moderate level. (2) The people in Klong Dan Sub-district municipality who had different ages, education levels, occupations, and income levels did have a difference in the participation behavior in the community in solid waste management with statistical significance at 0.05. And the people in the Klong Dan Subdistrict municipality who had different genders had no indifference in the participation behavior in community solid waste management. And (3) Knowledge and attitude were related in the same direction with the participation behavior in waste management with a statistical significance of 0.01, that is, the attitude toward waste management was coefficient correlated with the level of people’s participation behavior in community solid waste management in Khlong Dan Sub-district Municipality at a moderate level. (r = 0.522) Whereas, knowledge and understanding of waste management was coefficient correlated with the level of people’s participation behavior in community solid waste management in Khlong Dan Subdistrict Municipality at a low level (r = 0.164).